Gain Enhancement of Small Antenna Using Meander Line Concept - Venkata Narayana, M; Immadi, Govardhani.; Khan, Habibulla; Meena Kumari, Y (International Journal of Engineering and Technology, 2018)
In view with the latest technologies, compact device sizes had become a greater focus in industry because of which the demand for small antenna escalates. But electrically small antennas have high quality factor because of which the gain decreases. Therefore, an antenna was designed to improve the gain using the meander line concept based on the ground plane effect. A finite ground plane affects the resonant frequency and as the ground plane size increases, the resonant frequency decreases. By using a truncated ground plane, the antenna efficiency, gain and radiation pattern are improved. The antenna design had been modified based on another important concept of efficiently occupying the available volume. The antenna was designed on a cubic configuration and by using the two general techniques of modifying the geometry and truncating the ground plane, the gain of the antenna had been improved from 7.05dB to 8.03dB.Â